2022
DOI: 10.30541/v54i3pp.215-244
|View full text |Cite
|
Sign up to set email alerts
|

Which Pairs of Stocks should we Trade? Selection of Pairs for Statistical Arbitrage and Pairs Trading in Karachi Stock Exchange

Abstract: Pairs Trading refers to a statistical arbitrage approach devised to take advantage from short term fluctuations simultaneously depicted by two stocks from long run equilibrium position. In this study a technique has been designed for the selection of pairs for pairs trading strategy. Engle-Granger 2-step Cointegration approach has been applied for identifying the trading pairs. The data employed in this study comprised of daily stock prices of Commercial Banks and Financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Under the full short-selling restriction, all strategies, except the Hurst exponent approach, produce larger returns, with the cointegration method performing the best. In Pakistan's context, Qazi et al (2015) employed the Engle-Granger two-step tests of cointegration on commercial banks and the financial services sector listed on the Karachi Stock Exchange. The findings of this study showed that a linear short/long portfolio may be constructed from equities that are cointegrated and follow stationary dynamics.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Under the full short-selling restriction, all strategies, except the Hurst exponent approach, produce larger returns, with the cointegration method performing the best. In Pakistan's context, Qazi et al (2015) employed the Engle-Granger two-step tests of cointegration on commercial banks and the financial services sector listed on the Karachi Stock Exchange. The findings of this study showed that a linear short/long portfolio may be constructed from equities that are cointegrated and follow stationary dynamics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Table 2 showed mean, median and mode values along with max, min, and standard deviation of data from the central point under the cointegration method for both sectors, results illustrated that again both sectors had positive average values with the highest average returns of 0.0684 if portfolio consists of top 5 pairs in the non-financial sector. These findings are consistent with previous pair trading research in Pakistan, such as (Shaukat et al, 2021;Sohail., Sindhu & Imran., 2020;Qazi et al, 2015).…”
Section: Descriptive Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In context of Pakistan, there are handful of studies conducted on pair trading (Qazi et al, 2015;Sohail et al, 2020) and interestingly no one has considered the optimal stopping problem using stocks listed on Pakistan Stock Exchange (PSX). This study employs the novel entropic approach to explore the optimal boundary points that yield maximum profit for 64 companies listed on Pakistan Stock Exchange (PSX) for the period 2017-2019.…”
mentioning
confidence: 99%